2015
DOI: 10.2149/tmh.2015-01
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Survey of Severe Fever with Thrombocytopenia Syndrome Virus in Ticks in Nagasaki, Japan

Abstract: Severe fever with thrombocytopenia syndrome (SFTS) is an emerging disease endemic in East Asia. Transmitted to other organisms by infected ticks, the SFTS virus (SFTSV) and is endemic to Nagasaki in western Japan. However, epidemiological information regarding SFTSV in Nagasaki ticks has not been available to date. In this study, we began by examining the sensitivities of SFTSV gene detection by real-time RT-PCR and virus isolation in cultured cells and mice. These methods could detect SFTSV in the samples con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…The severe fever with thrombocytopenia syndrome virus (SFTSV) is a tick-borne emerging pathogen, causing high fever and drastic loss of leukocytes and platelets and multiorgan failure with high mortality in severe patients (12). There have been over 3000 cases reported in China since 2009 (13), and the virus has also been isolated recently in Japan and Korea and from patients and ticks (14,15). SFTSV possesses a genome with three ssRNA segments of negative sense, L, M, and S. Whereas the L segment encodes an RNA-dependent RNA polymerase, and M encodes two envelope proteins, Gn and Gc, the S segment, is an ambisense RNA with two opposite open reading frames encoding a nucleoprotein (NP) and a nonstructural protein (NSs) (12).…”
mentioning
confidence: 99%
“…The severe fever with thrombocytopenia syndrome virus (SFTSV) is a tick-borne emerging pathogen, causing high fever and drastic loss of leukocytes and platelets and multiorgan failure with high mortality in severe patients (12). There have been over 3000 cases reported in China since 2009 (13), and the virus has also been isolated recently in Japan and Korea and from patients and ticks (14,15). SFTSV possesses a genome with three ssRNA segments of negative sense, L, M, and S. Whereas the L segment encodes an RNA-dependent RNA polymerase, and M encodes two envelope proteins, Gn and Gc, the S segment, is an ambisense RNA with two opposite open reading frames encoding a nucleoprotein (NP) and a nonstructural protein (NSs) (12).…”
mentioning
confidence: 99%
“…SFTS caused by SFTSV infection was first emerged in China in 2009 [ 3 ], followed by reports from other Asian countries. At present no effective therapies or vaccines are available, and SFTS is associated with high rates of fatality [ 1 , 5 , 30 ]. In addition to reducing rates of tick bite, early diagnosis and treatment are important.…”
Section: Discussionmentioning
confidence: 99%
“…SFTSV was also detected in I. nipponensis ticks in South Korea [3]. A study in Japan suggested that SFTSV positivity rates were considered to be very low in ticks and viral loads were also very limited, as SFTSV was not detected in 2222 adult and nymph ticks collected from vegetation [26]. These results suggested that several tick species might act as vectors for SFTSV, however, the presence of viral RNA in ticks does not verify that the tick can transmit the virus.…”
Section: Transmission Of Sftsv To Animals By Ticksmentioning
confidence: 92%